Leading or Following? Women Learning Leadership Roles in Higher Education - Catherine A. Hansman (Adult Education Research Conference, 2007)
Women faculty members in higher education are reaching senior status at levels before unseen. Understanding both the challenges/obstacles and help these women received as they achieved advanced status will help future generations of women scholars who also aspire to a senior faculty position.